0318 An epidemiologic study of acute coronary syndrome in the working population. (23rd June 2014) - Chu, Po-Ching; Leon Guo, Yue; Juang, Jyh-Ming
Abstract : Objectives: Some of cardiovascular diseases, like stroke and acute coronary syndrome (ACS), are compensable diseases in Taiwan as well as Japan and Korea. The number of compensated cases in the disease has increased from 13 in 2006 to 92 in 2012. The information on workplace risk factors before onset of disease is rare, and this aim of this study is to conduct a case control study for analysing the association between ACS and work stress, using hospital-based study. Method: The study population was the patients in a medical centre. Questionnaire was designed based on literatures about non-work-related and work-related risk factors of cardiovascular diseases. The work-related factors included working time, working pattern, burnout scale, mental stress. The inclusion criteria of case group were workers more than 20 year-old, diagnosed with acute coronary syndrome and having job at onset. The inclusion criteria of control group were diagnosed without acute coronary syndrome and having job at recruitment. Results: There were 47 cases and 121 controls recruited. The results shows case group had larger percentage of male, alcohol intake, no intake of any healthy diet, and higher education level than control group. In addition, family history of premature AMI, history of diabetes, and history of current URI were more prevalent in case group. Multivariate logistic regression shows that smoking and night work were statistical significant factors associated with occurrence of acute coronary syndrome (OR=6.11, 3.59). Conclusions: When we think about the strategy on preventing cardiovascular diseases for working population, work-related factor, like night work, should be considering.